Tricky Stories: Settler-Academic Reflections on Anti-Colonial Teaching. Issue 2 (3rd July 2019) - Tamas, Sophie
Abstract : Personal stories and storytelling often appear as part of an effort to decolonize our approaches to teaching and learning. However, it can be difficult to develop adequately Indigenous-informed, anti-colonial storytelling practices, especially for non-Indigenous settler–academics and would-be allies situated in colonial institutions. The lessons learned from feminist or anti-oppressive narrative-based pedagogies might help but they do not account for Indigenous epistemic differences. In this paper, I reflect upon the questions and challenges that I encounter in my practice of using quasi–Indigenous stories to unsettle mainstream approaches to knowledge in the geography classroom. Rather than presenting a clear set of solutions, I hope to evoke and share the uncertainty that this work invites.